Critical factors in project success: a study of public sector construction projects in Malaysia / Wan Maimun Wan Abdullah - Wan Maimun, Wan Abdullah (2010)
The importance of the construction industry to nation building necessitates that project implemented achieves project success. However, studies and evidence have shown that there is a low probability in consistently achieving project success. Nevertheless, it seems that the definition of project success and how to achieve project success is quite illusive. For more than a century, researchers have been grappling with its definition but the concept remained ambiguous. From the early identification of time, cost and quality as elements of project success, researchers have added many other outcomes and objectives including stakeholders, project manager, communication, leadership, project management, organization structure, resources, contract and more. Later refinements separate these elements into success criteria and success factors. This research focuses on the success criteria of time, cost quality and stakeholders' appreciation and success factor groups of human management, process, organization, and contract and technical. The main aim of this research is to develop the components of project success and to identify the critical success factors. Other objectives are to find significant success criteria and to correlate these elements of project success. In addition the research statement emphasizes that human management is critical in the construction industry to ensure project success. The study adopts quantitative survey method and conducts a preliminary study and field survey using structured questionnaires. Data are analysed by quantitative techniques namely descriptive statistics, factors analysis and Pearson correlation. The findings of the study reveal that the ranking of success criteria in order of importance are 'Stakeholders' appreciation','Quality', 'Time' and 'Cost'. But most importantly the study identifies 'Human management' as the critical success factor group to achieve these success criteria. The subsequent ranking of the other success factor groups are 'Process', 'Contract and technical' and 'Organization'. Consequently, this study defines project success as achieving the success criteria of stakeholder's appreciation, completion as specified quality, within time and cost through the success factors of human management, process, contract and technical, and organization. The contribution of this study is to stamp the importance of human management in the construction industry. This awareness will be imperative to three main groups namely the stakeholders to give emphasis on human management in project implementation, the Construction Industry Development Board to review the project management training module, and the Institutions of Higher Learning to review project management programs giving emphasis concerning human management subjects.